A case on novel treatment protocol for difficult to treat foot myiasis - Dabhade, Mayur (International Journal of Advances in Medicine, 2022)
Foot myiasis is a rare condition, with only a few reported cases and no treatment consensus. We proposed a conservative and unique treatment approach with VAC dressing method. The patient administered in the hospital with presentation of deep tissue injury from a sharp stone, from 3 months back which was maggot infested. The patient had approached local physicians before been admitted in our facility. The wound was severe with maggot infestation. The patient was non diabetic with no other comorbid conditions. We had the aim of infection free wound with faster rate of healing, which was fulfilled by the novel treatment protocol using vacuum-assisted closure (VAC®) dressing method. Culture sensitivity tests ruled out infection and maggot infestation. The wound was closed surgically after healthy uninfected granulation tissue confirmed with culture sensitivity report. No recurrence of maggot or any other infection were found. The protocol performed was safe and effective in critical case of myiasis.